Sustainable Marketing Development Strategy of Bakery and Coffee Teaching Factory Politeknik Negeri Jember - Iskandar, Ridwan; Retnowati, Naning; Malika, Uyun (P3M Politeknik Negeri Jember, 2024)
Bakery and Coffee Teaching Factory faces challenges in developing their marketing strategy such as marketing range, quality standard with the producer of the same products, and ability to make a product as the customer desired precisely. These will threaten the sustainability dimensions of Tefa Bakery and Coffee Politeknik Negeri Jember. Thorough efforts shall be made to overcome those problems by identifying the sustainability attributes, especially on the social, economic, and environmental dimensions. Later, the efforts shall be synchronized to the policy of the institution to improve the main performance indicator of Politeknik Negeri Jember. The problems of this research include what attributes that become the leverage factors, how the leverage factors related to the strategy, and what policy that could improve the main performance indicator. This research aims to: formulate the marketing development sustainability dimensions and formulate performance improvement priority strategy in developing Tefa. Research method: analysing sustainability through multidimensional scaling technique; processing data by using application R that includes analysis of ordination, leverage, monte carlo, and kite diagram. The targeted output covers: levelled marketing development strategy based on the level of importance and Tefa development policy that combines the bottom-up development strategy and institutional policy. The results showed that the environmental dimension is less sustainable, the social dimension is less sustainable, and the economic dimension is quite sustainable.